2021
DOI: 10.1088/1361-6641/abd959
|View full text |Cite
|
Sign up to set email alerts
|

A low turn-on voltage AlGaN/GaN lateral field-effect rectifier compatible with p-GaN gate HEMT technology

Abstract: In this paper, we designed a low turn-on voltage (V On) AlGaN/GaN lateral field-effect rectifier (LFER) compatible with p-GaN gate high-electron-mobility transistor (HEMT) technology (PG-LFER). We also established an analytical model on the gated control two-dimensional-electron-gas density (n S) distributions and V On to investigate the underlying mechanism. The designed PG-LFER features a p-GaN charge storage layer (CSL) under the anode terminal. Net nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…Various device structures, such as fluoride ion implantation, pillar structure, and field coupling gate, have been proposed and explored to address this issue [16][17][18]. Additionally, extensive studies from our group and others have demonstrated that p-GaN on HEMT is a charming strategy for the realization of the enhancement-type GaN HEMTs based on the process in contemporary foundries [19][20][21][22][23]. Despite these efforts, the low concentration of the thin 2DEG still limits the current transportation, preventing the device from reaching its full potential [24].…”
Section: Introductionmentioning
confidence: 99%
“…Various device structures, such as fluoride ion implantation, pillar structure, and field coupling gate, have been proposed and explored to address this issue [16][17][18]. Additionally, extensive studies from our group and others have demonstrated that p-GaN on HEMT is a charming strategy for the realization of the enhancement-type GaN HEMTs based on the process in contemporary foundries [19][20][21][22][23]. Despite these efforts, the low concentration of the thin 2DEG still limits the current transportation, preventing the device from reaching its full potential [24].…”
Section: Introductionmentioning
confidence: 99%